A Distributional Analysis of Public–Private Wage Differential in India. (8th October 2015) - Azam, Mehtabul; Prakash, Nishith
Abstract: In this paper, we examine public–private wage differential among men in India across the entire wage distribution. We find that the raw wage gap between public and private sector is positive across the entire wage distribution in both urban and rural areas. A quantile regression‐based decomposition reveals that that the public sector workers enjoy a positive wage premium across the entire wage distribution in both urban and rural areas, although the magnitude of wage premium is smaller at the top quantiles.